Vapor-deposited iron sulfide films as a novel hydrogen permeation barrier for steel: Deposition condition, defect effect, and hydrogen diffusion mechanism. (9th August 2018) - Luo, Bingwei; Bai, Pengpeng; An, Teng; Zhang, Shuai; Wen, Xiangli; Chen, Liqiang; Zheng, Shuqi
Abstract: Hydrogen embrittlement is a serious problem in the oil/gas industry. In this work, various iron sulfide (FeS) films, including iron monosulfide (FeS), pyrite (FeS2 ), and pyrrhotite (Fe7 S8 ), were synthesized in X80 steel by chemical vapor deposition at 200 °C, 300 °C, 400 °C, and 500 °C. The corrosion resistance and hydrogen permeation properties of the FeS films were investigated through electrochemical methods. Results indicated that FeS films significantly improved the hydrogen barrier properties of the X80 steel, which was closely related to the crystal structure type and defects of FeS films. Defects like microcracks and pinholes during deposition can increase the porosity of the film, resulting in the film properties decreased. Moreover, FeS film (at 300 °C), which had the smallest apparent hydrogen diffusivity ( D  ˜ 2.64 × 10 −7  cm 2 /s) and apparent subsurface concentration ( C app  ˜ 1.12 μmol/cm 3 ), had the best hydrogen barrier properties. The corrosion resistance of FeS film (300 °C) was excellent. Highlights: FeS films are synthesized by CVD method. FeS film (at 300 °C) has excellent corrosion resistance. FeS films are novel hydrogen permeation barrier. Film defects reduce the hydrogen barrier properties of FeS film.